The availability, price, and marketing characteristics of organic foods and beverages: a comparative food environment assessment - Sadler, Alexandra; Bharath, Yandrapu; Tereza da Silva, Jacqueline; Abreu, Daniel Carneiro de; Shankar, Emily; Bassetto, Karolyne Vieira; Jaacks, Lindsay (Frontiers in Sustainable Food Systems, 2025)
BackgroundDemand for organic foods remains low, despite the potential of organic products to contribute to sustainable food systems. Food purchasing decisions are influenced by the food environment, yet no study has systematically evaluated food environment dimensions for organic products.MethodsWe developed an organic food environment assessment tool that evaluates the availability, price, vendor and marketing characteristics of organic foods in urban food environments. We implemented the tool in nine cities across Brazil, India, and the United Kingdom for 14 sentinel products.ResultsWe found that only 37% of 808 surveyed vendors sold an organic option. Organic rice was 1.8–2.5 times the price of non-organic rice. Only 8% of organic products used a price promotion, while 62% displayed a certification label. In India, health benefits were the predominant marketing message (59% of organic foods); in the UK, it was environmental benefits (50%).ConclusionOur findings indicate a need for a more evidence-based strategy in marketing organic foods and beverages to consumers. There is a need for further research and implementation of market-side initiatives to boost demand for organic foods and beverages in order to encourage a shift towards more sustainable food systems.